INJECTION PROPAGATION MODEL IN SANDY SOIL - Petrovskiy, A. F.; Babiy, I. N.; Borisov, A. A. (Academic journal Industrial Machine Building Civil Engineering, 2017)
This articles focuses on the process of injection solution in the sand as physical phenomena. During theoretical studies of the propagation of the fluid phase in a porous medium, actual is the definition of the parameters of the jet, necessary for layer material discontinuity in the contact zone of the jet to the surface. It can be achieved through the injection process modeling in a dispersion medium by constructing geometrical similarity of injection jet. It is found that the propagation of the fluid phase in the solid body pores suggests that as they reach the point at the distance from the injector to the «end» of the jet in pores pre-saturated by water, gradual change in injection rate depending on the initial rate of efflux and viscosity occurs.